Desafios jurídicos na era das Fake News: regulação das redes sociais e normas legais - Tonial, Tálison Battistella (2024)
The objective of this article is to carry out an analysis of the understanding of fake news within the scope of the Judiciary. The issue arises from the need to balance the right fundamental freedom of expression of thought and information, with the need to protect other legally protected rights and assets that may be affected by the exercise of this law in the most diverse media. Thus, the problem arises: until point the individual right of expression can be limited to curb the spread of fake news in the media, guaranteeing the right to freedom of expression, but protecting other human rights? To answer this question, we used bibliographical research based on the hypothetical deductive method. It is concluded that it is done appropriate legislation and the collaboration of large technology companies are necessary to ensure freedom of expression in communication channels and hold those accountable spreaders of fake news.